2011
DOI: 10.3233/xst-2011-0311
|View full text |Cite
|
Sign up to set email alerts
|

Novel applications of diagnostic X-rays in activating a clinical photodynamic drug: Photofrin II through X-ray induced visible luminescence from "rare-earth" formulated particles

Abstract: Introduction: In this communication we report on a novel non-invasive methodology in utilizing "soft" energy diagnostic X-rays to indirectly activate a photo-agent utilized in photodynamic therapy (PDT): Photofrin II (Photo II) through X-ray induced luminescence from Gadolinium Oxysulfide (20 micron dimension) particles doped with Terbium: Gd2O2S:Tb. Photodynamic agents such as Photo II utilized in PDT possess a remarkable property to become preferentially retained within the tumor's micro-environment. Upon th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 27 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…Since then, several rare‐earth‐element‐based nanoparticles (e.g., LaF 3 :Ce, LaF 3 :Tb, Tb 2 O 3 , Gd 2 O 2 S:Tb, etc.) have been used as X‐ray converter in X‐PDT …”
Section: X‐ray‐excited Synchronous/synergistic Therapymentioning
confidence: 99%
“…Since then, several rare‐earth‐element‐based nanoparticles (e.g., LaF 3 :Ce, LaF 3 :Tb, Tb 2 O 3 , Gd 2 O 2 S:Tb, etc.) have been used as X‐ray converter in X‐PDT …”
Section: X‐ray‐excited Synchronous/synergistic Therapymentioning
confidence: 99%
“…In addition, work performed by Abliz et al . and Zou et al . have also shown that micronic scintillators mixed to a PS may also produce ROS using only radiative energy transfer.…”
Section: Introductionmentioning
confidence: 90%
“…Abliz et al . described the excitation of Photofrin‐II through energy transfer from gadolinium oxysulfide particles (20 μm diameter) doped with terbium Gd 2 O 2 S:Tb 3+ . Persistent luminescent NPs conjugated with PSs excited by X‐ray can emit luminescence able to activate the PSs; as a consequence 1 O 2 is produced, which strengthens the radio effect .…”
Section: Introductionmentioning
confidence: 99%
“…Most of these “proof of concept” studies are restricted to optical measurements (emission spectra, fluorescence decay, 1 O 2 chemical probes fluorescence properties) 105, 106 or in vitro experiments demonstrating reduction in viability due to nanoscintillator based PDT. For example, Abliz et al reported a reduction in viability of human glioblastoma cells, from 80% to 10%, when micrometric gadolinium oxysulfide particles were combined with Photofrin II and irradiated with X-rays 107.…”
Section: Forward Looking Methodologies For Deep Tissue Pdtmentioning
confidence: 99%